Identification of high-risk soil erosion areas in the central Yunnan urban agglomeration and the differentiated driving mechanisms compared to the overall agglomeration - Dongling Ma; Shuangyun Peng; Zhiqiang Lin; Bangmei Huang; Ziyi Zhu; Shuangfu Shi (Scientific Reports)
Abstract Revealing the complex driving mechanisms of soil erosion is essential for assessing regional ecological security. Focusing on the Central Yunnan Urban Agglomeration (CYUA), a typical mountainous urban region, this study analyzed the spatiotemporal dynamics of soil erosion from 1990 to 2020 using the RUSLE model and the Improved Stability Mapping (STD) method, identifying high-risk soil erosion areas. Additionally, it applied the OPGD and MGWR models to reveal differentiated driving mechanisms of soil erosion across the urban agglomeration and in high-risk zones. The results indicated that (1) over the past three decades, approximately 27.56% of the CYUA experienced soil erosion, with moderate and high-intensity erosion accounting for 7.04% and 3.83%, respectively. Soil erosion increased continuously from 1990 to 2000 but showed significant improvement after 2000. (2) High-risk areas identified using the improved STD method were primarily distributed along riverbanks, which are highly sensitive to external disturbances. (3) Slope and vegetation were the key factors affecting the overall soil erosion pattern in the urban agglomeration, while rainfall and vegetation were the dominant influencing factors in high-risk areas, where spatial heterogeneity of driving factors was lower than in the general region. (4) Vegetation cover had a significant mitigating effect on soil erosion, making increased vegetation coverage an effective strategy for soil and water conservation. This study provides new insights for soil erosion risk assessment and offers a scientific basis for regional soil erosion control and ecological restoration.